Berakhirnya Pernikahan di Indonesia dan Dampaknya Terhadap Hukum Islam dan Hukum Positif - Fajri Masaid; Hafifa Hafifa; Elvita Sarah Azzahra; Wismanto Wismanto (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
the dissolution of a marriage or marriage is a complex event that has significant legal meaning, both from the perspective of Islamic law and positive law in Indonesia. In Islam, divorce is seen as a last resort that is not recommended, but is still recognized as a reality. The aim of this research is to examine and understand Munakahat fiqh which discusses the breakdown of marriage and the consequences it causes. The method used in this research is a qualitative method with a literature review. The main source of information is obtained from reading materials, namely books, magazines and related articles. The results of this research conclude that the dissolution of marriage in Islamic law means that divorce processes such as talak, fasakh, or khul' must be regulated with full justice, decency and prudence. Both parties must obtain their rights in a fair manner, including property rights, maintenance and child care. The importance of maintaining family unity and avoiding divorce except in circumstances that really need to be emphasized in Islamic teachings. In addition, Islamic law encourages peaceful resolution of conflicts and solutions that respect the rights of all parties involved. By understanding the relevant principles of Islamic law and seeking guidance from qualified clerics and legal experts, Muslims can handle the dissolution of marriage wisely, prioritizing mutual welfare, and maintaining the moral and ethical values ​​taught by the Islamic religion.